2014
DOI: 10.1007/s12026-014-8527-y
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the FAK family kinases in T cells: beyond actin cytoskeletal rearrangement

Abstract: T cells control the focus and extent of adaptive immunity in infectious and pathological diseases. The activation of T cells occurs when the T cell antigen receptor (TCR) and costimulatory and/or adhesion receptors are engaged by their ligands. This process drives signaling that promotes cytoskeletal rearrangement and transcription factor activation, both of which regulate the quality and magnitude of the T cell response. However, it is not fully understood how different receptor-induced signals combine to alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 95 publications
1
38
0
Order By: Relevance
“…EB1 and AIM2 inflammasomes were shown to colocalize with γ-tubulin in the perinuclear region (i.e., the microtubule organizing center; MTOC) in macrophages subjected to poly(dA:dT) stimulation1925. Pyk2 and FAK also localize with the MTOC via an association with paxillin, and thereby control microtubule polymerization and MTOC polarization1617. This suggests that Pyk2 and FAK may regulate microtubule polymerization and MTOC polarization in response to NLRP3 stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EB1 and AIM2 inflammasomes were shown to colocalize with γ-tubulin in the perinuclear region (i.e., the microtubule organizing center; MTOC) in macrophages subjected to poly(dA:dT) stimulation1925. Pyk2 and FAK also localize with the MTOC via an association with paxillin, and thereby control microtubule polymerization and MTOC polarization1617. This suggests that Pyk2 and FAK may regulate microtubule polymerization and MTOC polarization in response to NLRP3 stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Pyk2 and FAK are multifunctional proteins that primarily promote cell migration by controlling the disassembly of focal adhesions to extend the leading edge and retract the trailing edge. Integrin-ligand interactions activate Pyk2 and FAK in part by triggering their autophosphorylation at Tyr402 and Tyr397, respectively1617. This, in turn, controls the rearrangement of the actin cytoskeleton by regulating Rho and Rac signals16.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FAK is recruited to FAs in response to integrin-mediated cell adhesion. However, FAK is also involved in signalling of other cell surface receptors (including G protein-coupled receptors, the T cell receptor, the deleted-in-coloncancer netrin receptor and transmembrane tyrosine kinases) and is acting in many cellular environments, such as lamellipodia, microtubules and the nucleus (Chapman and Houtman, 2014;Schaller, 2010;Zhao and Guan, 2009). FAK can promote different effects in the same subcellular localisation (such as assembly and disassembly of FAs); it can also produce convergent effects at different subcellular localisations (such as cancer cell invasion and metastasis in lamellipodia or the nucleus) (Arold, 2011;Cance and Golubovskaya, 2008;Hall et al, 2011;Schaller, 2010).…”
Section: Multiple Cellular Functions Of Fakmentioning
confidence: 99%
“…Pyk2 can be activated in T cells through various cell stimuli, including TCR (9-11) and integrin ligands (12,13). Despite numerous studies examining Pyk2 activation in T cells, there is no clear consensus on how Pyk2 activation downstream of TCR and integrins influences T cell activation (14). Examination of Pyk2-deficient mice indicated that Pyk2 is important for some aspects of cell polarization and migration in several immune cell types.…”
mentioning
confidence: 99%